Compliance with reduced-impact harvesting guidelines by timber enterprises in terra firme forests of the Brazilian Amazon - Pokorny B.; Sabogal, C.; Silva, J.N.M.; Bernardo, P.; Souza, J.; Sweede, J. (2005)
The paper presents the results and main conclusions of an assessment of compliance with technical guidelines for Reduced Impact Harvesting (RIH) in terra firme forests of the Brazilian Amazon. The assessment was carried out in two certified timber enterprises in the State of Para, Brazil applying the RIH-guidelines for a period of over three years. From a tool developed for Amazonian forest enterprises to monitor the sustainability of their harvesting operations, which uses a set of criteria and indicators (C&I), a total of 190 verifiers were selected for assessing the 61 RIH-guidelines. The assessment revealed valuable information with regard to the state of implementation and quality of the forest operations in the two enterprises and important insights for improvement of the RIH-guidelines. Two thirds of the RIH-guidelines were fully implemented. Their acceptance, however, differed according to the situation and interest of the enterprises. Among the reasons for incomplete implementation of the RIH-guidelines, the lack of systematic monitoring, insufficient training and qualification, and inadequate equipment appeared to be most important. The study also showed the need for the continuous assessment of the quality and relevance of RIH-guidelines.